PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF STUDENT TEAM ACHIEVEMENT DIVISION DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR AL-QUR’AN HADITS SISWA MADRASAH TSANAWIYAH NEGERI 3 SIMALUNGUN - Nurhayati Nurhayati (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The purpose of this study was to find out: (1) the effect of the applicationof STAD cooperative learning strategies to the learning outcomes of Al-Qur'an Hadiths of Simalungun MTs Negeri 3 students, (2) the effect oflearning activities on learning outcomes of Al-Qur'an Hadith students ofMTs Negeri 3 Simalungun, (3) the interaction of the application of STADcooperative learning strategies and learning activities to the learningoutcomes of Al-Qur'an Hadith students of Simalungun MTs Negeri 3.This type of research is quantitative research with research methods usedare experiments. The population of this study were all class VIII whichconsisted of 5 classes. The sampling technique is used cluster randomsampling. This technique was chosen because what was sampled from thepopulation was the number of classes (as many as 5 classes) rather thanthe number of students in the population. STAD cooperative learningstrategy class is class VIII1 with 36 students and Class VIII3 as expositorylearning class with 38 students. The data collection technique is a learningoutcome test and questionnaire. Data analysis technique is analysis ofvariance tested at α = 0.05. Findings The results of the study were: (1) theaverage learning outcomes of students taught with STAD cooperativelearning strategies = 28 higher than the average student learning outcomestaught with expository learning strategies = 26.95, with Fcount = 27.44 >Ftable = 3.98, (2) the average student learning outcomes with high learningactivities = 29.61 higher than student learning outcomes with low learningactivities = 26.07 with Fcount = 6.17> Ftable = 3.98, and (3) there is aninteraction between learning strategies and learning activities towardsCivics learning outcomes with Fcount = 18.27 > Ftable = 3.98.